Glutathione S‐transferase omega 1 inhibition activates JNK‐mediated apoptotic response in breast cancer stem cells. (5th April 2019) - Manupati, Kanakaraju; Debnath, Sudhan; Goswami, Kalyan; Bhoj, Priyanka S.; Chandak, Hemant S.; Bahekar, Sandeep P.; Das, Amitava
Abstract : Glutathione S ‐transferase omega 1 (GSTO1) contributes to the inactivation of a wide range of drug compounds via conjugation to glutathione during phase reactions. Chemotherapy‐induced GSTO1 expression in breast cancer cells leads to chemoresistance and promotes metastasis. In search of novel GSTO1 inhibitors, we identified S2E, a thia‐Michael adduct of sulfonamide chalcone with low LC50 (3.75 ± 0.73 μm ) that binds to the active site of GSTO1, as revealed by molecular docking (glide score: −8.1), cellular thermal shift assay and fluorescence quenching assay ( K b  ≈ 10 × 10 5  mol·L −1 ). Docking studies confirmed molecular interactions between GSTO1 and S2E, and identified the hydrogen bond donor Val‐72 (2.14 Å) and hydrogen bond acceptor Ser‐86 (2.77 Å). Best pharmacophore hypotheses could effectively map S2E and identified the 4‐methyl group of the benzene sulfonamide ring as crucial to its anti‐cancer activity. Lack of a thiophenyl group in another analog, 2e, reduced its efficacy as observed by cytotoxicity and pharmacophore matching. Furthermore, GSTO1 inhibition by S2E, along with tamoxifen, led to a significant increase in apoptosis and decreased migration of aggressive MDA‐MB‐231 cells, as well as significantly decreased migration, invasion and mammosphere formation in sorted breast cancer stem cells (CSCs, CD24 − /CD44 + ). GSTO1 silencing in breast CSCs also significantly increased apoptosis and decreased migration. Mechanistically, GSTO1 inhibition activated the c‐Jun N‐terminal kinase stress kinase, inducing a mitochondrial apoptosis signaling pathway in breast CSCs via the pro‐apoptotic proteins BAX, cytochrome c and cleaved caspase 3. Our study elucidated the role of the GSTO1 inhibitor S2E as a potential therapeutic strategy for preventing chemotherapy‐induced breast CSC‐mediated cancer metastasis and recurrence. Abstract : In breast cancer stem cells (CSCs) sorted from aggressive triple negative breast cancer, chemotherapeutics induce the expression of glutathione S ‐transferase omega 1 (GSTO1), which confers chemoresistance. We identified S2E, a thia‐Michael adduct chalcone with drug‐like properties, as a compound that binds to the active site of GSTO1 and, along with chemotherapeutics, inhibits breast CSC proliferation, migration, invasion and mammosphere formation. The inhibition of GSTO1 activates the JNK stress kinase, which induces downstream mitochondrial apoptotic signaling.